HUBUNGAN BERAPA KARAKTERISTIK ANAK DENGAN OBESITAS - Mifbakhuddin . . (Jurnal Kesehatan Masyarakat Indonesia, 2003)
ABSTRACT Background: The first long term development has just been passed. It gives many achievements in social, cultural, health, educational, and economic aspects. Following the positive and negative effects of the national development, The disease pattern changes. Some cases such as infection disease and nutritious lackness are decreasing now. In the contrary, degenerative disease and cancer are increasing in numbers. A new problem also takes a place. Over nutrient emerges into serious matter. Objective: Analyses the relationship characteristics with obesity in State Favorite Elementary School in Kecamatan Semarang Timur Kota Semarang. Methods : Type of this research is exploracy survey with cross sectional study. Population of this study is all of the obese students of state favorite elementary school. All of them will be observed. Data is analyzed descriptively and analytically. The independent variables are sex, age, genetic, intake of energy, economic and mother's education levels, and the independent is prevalence of obese. Results: Research describes that the whole prevalence is 6.72 %. Prevalence of girl’s obesity is 7.82% while the boy is 5.69%. From 73 sample, 32 (43.83%) are boys and 4l (56.17%) a girls. Most samples (so <76%o) are children from 10 to 12 Years old. It is followed by the children it age af 7 to 9 years old (about 8.36%) and < 6 years old (10.97%). Research also shows us that 54.80% mothers are educated in formal school for about > 13 years. Forty six families (63.01%) get income >_Rp 350.000,00, but the total average noume of all family k Rp.345.000,00. Fifty nine family (80.82%) from all those family have genetic element of being fat (obesity). Conclusion: there are correlations among all variables, except sexual variable. Effective contribution indicates that food consumption takes the first order (46.9%) Keywords: obesity, characteristics of students, Favorite Elementary School